2013
DOI: 10.17511/ijmrr.2013.i03.05
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of streptococcal infection with reference to Rheumatic fever

Abstract: Introduction: Group A hemolytic streptococcal infections have a worldwide distribution among children and it poses an important health problem globally. Group A streptococcal (GAS) serology is used for the diagnosis of post-streptococcal diseases, such as acute rheumatic fever, post-streptococcal Glomerulonephritis and occasionally for the diagnosis of streptococcal pharyngitis. Upper normal limits for streptococcal serology should be determined for individual populations because of differences in the epidemio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
1
2
0
1
Order By: Relevance
“…ULN values has traditionally been used as a single estimated cutoff value for diagnosing recent streptococcal infection in ARF, which is late sequelae of Group A streptococcal infection a rising titer cannot be demonstrated for lack of an earlier estimation being done. ULN values of ASO and ABD in normal healthy children in our study population were 262 IU/ml and 134 IU/ml, respectively, and comparative values from other geographical areas are reported by Sethi et al ,[7] Une et al ,[11] Mahendrappa,[12] and Karmarkar et al [13] [Table 2]. Lower values in our study again reflect the need to have local regional values for different populations.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…ULN values has traditionally been used as a single estimated cutoff value for diagnosing recent streptococcal infection in ARF, which is late sequelae of Group A streptococcal infection a rising titer cannot be demonstrated for lack of an earlier estimation being done. ULN values of ASO and ABD in normal healthy children in our study population were 262 IU/ml and 134 IU/ml, respectively, and comparative values from other geographical areas are reported by Sethi et al ,[7] Une et al ,[11] Mahendrappa,[12] and Karmarkar et al [13] [Table 2]. Lower values in our study again reflect the need to have local regional values for different populations.…”
Section: Discussionsupporting
confidence: 80%
“…The rise in ADB is delayed, well beyond the sampling for acute pharyngitis and hence not documented in this group of patients. Comparative data of ASO in Acute pharyngitis by Kotby et al ,[9] Machado et al ),[15] and Une et al [11] are shown in Table 3.…”
Section: Discussionmentioning
confidence: 99%
“…Acute rheumatic fever is an autoimmune disease that follows infection with GAS; however, the isolation of GAS is uncommon (<15%), and so confirmation of the diagnosis often relies on streptococcal antibody tests. 5 While a number of tests utilize different antigens of GAS, the most frequently performed tests are those that determine the anti-streptolysin O (ASO) titer and the anti-DNase B (ADB) titer. Ideally, it is recommended that the titer be determined in the acute phase and then determined in the convalescent phase 14 to 28 days later, with a positive result defined as a rise in titer of twofold or more.…”
Section: Discussionmentioning
confidence: 99%
“…Так как высокий уровень АСЛ-О может быть обусловлен недавно перенесенной острой стрептококковой инфекцией, которая совпала с проявлениями артрита, но не является причиной его возникновения [13]. Ложноположительные титры АСЛ-О выявляются у пациентов с гиперлипидемией, вызванной билиарной обструкцией печени, нефрозом и миеломной болезнью [14]. Можно сделать выводы, что сопутствующая соматическая патология, наличие случайно присоединившейся вирусной инфекции в совокупности с повышением титра АСЛ-О приводит к неправильным выводам о наличии А-стрептококковой инфекции у пациента.…”
unclassified